In Vivo Two-Photon Imaging Analysis of Dynamic Degradation of Hepatic Lipid Droplets in MS-275-Treated Mouse Liver - Lee, Chang Gun; Lee, Soo Jin; Park, Seokho; Choi, Sung E.; Song, Min Woo; Lee, Hyo Won; Kim, Hae Jin; Kang, Yup; Lee, Kwan Woo; Kim, Hwan Myung; Kwak, Jong Young; Lee, In Jeong; et al. (International Journal of Molecular Sciences, 2022)
The accumulation of hepatic lipid droplets (LDs) is a hallmark of non-alcoholic fatty liver disease (NAFLD). Appropriate degradation of hepatic LDs and oxidation of complete free fatty acids (FFAs) are important for preventing the development of NAFLD. Histone deacetylase (HDAC) is involved in the impaired lipid metabolism seen in high-fat diet (HFD)-induced obese mice. Here, we evaluated the effect of MS-275, an inhibitor of HDAC1/3, on the degradation of hepatic LDs and FFA oxidation in HFD-induced NAFLD mice. To assess the dynamic degradation of hepatic LDs and FFA oxidation in fatty livers of MS-275-treated HFD C57BL/6J mice, an intravital two-photon imaging system was used and biochemical analysis was performed. The MS-275 improved hepatic metabolic alterations in HFD-induced fatty liver by increasing the dynamic degradation of hepatic LDs and the interaction between LDs and lysozyme in the fatty liver. Numerous peri-droplet mitochondria, lipolysis, and lipophagy were observed in the MS-275-treated mouse fatty liver. Biochemical analysis revealed that the lipolysis and autophagy pathways were activated in MS-275 treated mouse liver. In addition, MS-275 reduced the de novo lipogenesis, but increased the mitochondrial oxidation and the expression levels of oxidation-related genes, such as PPARa, MCAD, CPT1b, and FGF21. Taken together, these results suggest that MS-275 stimulates the degradation of hepatic LDs and mitochondrial free fatty acid oxidation, thus protecting against HFD-induced NAFLD.
Keywords: fatty liver; FGF21; intravital imaging; mitochondrial oxidation; MS-275; NAFLD